PENGARUH IMPLEMENTASI KURIKULUM MERDEKA TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN MATEMATIKA KELAS V SD NEGERI 26 SINGKAWANG - Norlina Sariningsih; Safrihady; Dewi Mariana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to evaluate the implementation of the Merdeka Curriculum with a teaching module on fractional values in grade V SD Negeri 26 Singkawang and its impact on student learning outcomes. The study used a pre-experimental design with a one-group pretest-posttest design. The sample consisted of 23 grade V students. Data was collected through observations of curriculum implementation and multiple-choice tests to measure student learning outcomes. The results show: (1) The implementation of the Merdeka Curriculum achieved a success rate of 75%, categorized as high; (2) Student learning outcomes improved from an average pre-test score of 50 to 81 on the post-test; (3) Paired Sample T-Test analysis revealed a significant effect on learning outcomes, with a sig (2-tailed) value of < 0.00, indicating the rejection of Ho and acceptance of Ha. These findings suggest that the implementation of the Merdeka Curriculum positively impacts student learning outcomes.